Lipiodol retention pattern assessed by cone beam computed tomography during conventional transarterial chemoembolization of hepatocellular carcinoma: accuracy and correlation with response. Issue 1 (December 2016) - Hu, Jungang; Maybody, Majid; Cao, Guang; Wang, Xiao; Chen, Hui; Zhu, Xu; Yang, Renjie; Wang, Xiaodong
Abstract Background To investigate accuracy of intraprocedural cone beam computed tomography (CBCT) compared to fluoroscopy for detection of lipiodol retention pattern during conventional transarterial chemoembolization (cTACE) of hepatocellular carcinoma (HCC) and its correlation with short-term response. Methods Between September 2013 and July 2014, 29 patients with HCC underwent chemoembolization of 51 tumors (mean diameter 28.1 mm, range 10.0–136.3 mm). Lipiodol retention pattern was assessed by CBCT at the endpoint of cTACE compared by fluoroscopy. Depending on the pattern of tumor covered by lipiodol three classes were defined: complete (more than 90 %, no peripheral defects), moderate (50–90 %, some with or without peripheral defects), and poor (less than 50 %). Tumor response was assessed by modified Response Evaluation Criteria in Solid Tumors (mRECIST) based on follow-up contrast enhanced (CE) computed tomography (CT) or magnetic resonance imaging (MRI) obtained 4–6 weeks post-cTACE. Correlations between lipiodol retention patterns on CBCT and fluoroscopy as well as tumor response were assessed using multivariate logistic regression. Results Of 51 hepatic tumors, 40 (78.4 %) had complete response (CR); 8 (15.7 %) had partial response (PR); 1 (2.0 %) had stable disease (SD); and 2 (3.9 %) had progressive disease (PD). The degree of lipiodol retention scored excellent, moderate, and poor, in fluoroscopic images vs CBCT images were 23 (45.1 %) vs 39 (76.5 %), 19 (37.3 %) vs 11 (21.6 %), and 9 (17.6 %) vs 1 (2.0 %), respectively. Lipiodol retention assessment with CBCT (Az = 0.75) is more accurate than fluoroscopy (Az = 0.54) in predicting target tumor response. Other than lipiodol retention pattern assessed with CBCT (p = 0.01), tumor size (p = 0.04) is an independent predictors of CR. Conclusion CBCT is more accurate than fluoroscopy in classification of lipiodol retention pattern in HCC tumors at the time of cTACE. CBCT could be used as a reliable intra precedural monitoring modality of cTACE.